PEMBERDAYAAN MASYARAKAT MELALUI PEMBANGUNAN BERBASIS “SKP2” TERPADU DALAM MEWUJUDKAN “BLUE ECONOMY” MASYARAKAT PESISIR PANTAI DAN KEPULAUAN YANG TANGGUH DAN SEJAHTERA (TARA) - Linda Suwarni; Helman Fachri; Iskandar Arfan (Jurnal Buletin Al-Ribaath, 2017)
Sungai Raya Kepulauan District is located on the coast separately and away from the Bengkayang Capital. The majority of the population including the coastal communities who work as fishermen. The coastal area has great potential but has not been used optimally. As a result, various problems arose, for example, the low level of health in the village, lack of public education because of limited school and lack of community economy further aggravate the situation. Therefore, we need a new concept for the development of coastal areas, namely the "Blue Economy". As for the measures to be implemented in the framework of the completion of the above problems through Community Empowerment Through Driven Development "SKP2" (Health, Fisheries, and Economic) Integrated In Realize "Blue Economy" Coastal Community and Islands Tough and Welfare (TARA), among others: (a) Enhanced Behavior clean and healthy Lifestyle (PHBs), the method which is used to overcome the problems, namely: workshop, health promotion include counseling on health behavior, socialization healthy latrines, clean water supply, sanitation, training of cadres teen idle and cadres posyandu, family formation standby and idle teenagers, socialization of ground use for medicinal plant families, provision of CPTS (Hand washing), and simple clean water filtration; (b) Increasing the entrepreneurial economy of agriculture and fisheries, methods which are used to overcome the problems, namely: the establishment and development of women farmers, making training Aquaponics pool tarp and net cages step, training cultivation and increasing fish production, training of fisheries product processing, training nursery plantation processing, processing of tourist management training, socialization packaging fishery products and plantations. (c) Improving education in an effort to support the government's compulsory education (12 years old), the method that used to overcome the problems, namely: the establishment of "Smart House B2" smart house B2 cadre training, training on making collages, mosaics and montage of simple materials, training methods Morance, cadre training education, and training management "Smart House B2”. Keywords: health behavior, Entrepreneurship Agricultural Economics, SKP2, Blue Economy, Coastal Communities